Influence of Reflow Cycles of the Pb–Free/Pb Hybrid Assembly Process on the IMCs Growth Interface of Micro-Solder Joints - Xinyuan He; Qi Zhang; Qiming Cui; Yifan Bai; Lincheng Fu; Zicong Zhao; Chuanhang Zou; Yong Wang (Crystals, 2025)
Under the dual impetus of environmental regulations and reliability requirements, the Pb–free/Pb hybrid assembly process in aerospace-grade ball grid array (BGA) components has become an unavoidable industrial imperative. However, constrained process compatibility during single or multiple reflow protocols amplifies structural heterogeneity in solder joints and accelerates dynamic microstructural evolution, thereby elevating interfacial reliability risks at solder joint interfaces. This paper systematically investigated phase composition, grain dimensions, thickness evolution, and crystallographic orientation patterns of interfacial intermetallic compounds (IMCs) in hybrid micro-solder joints under multiple reflows, employing electron backscatter diffraction (EBSD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). The result shows that the first reflow induces prismatic Cu6Sn5 grain formation driven by Pb aggregation zones and elevated Cu concentration gradients. Surface-protruding fine grains significantly increase kernel average misorientation (KAMave) of 0.68° while minimizing crystallographic orientation preference density (PFmax) of 15.5. Higher aspect ratios correlate with elongated grain morphology, consequently elevating grain size of 5.3 μm and IMC thickness of 5.0 μm. Subsequent reflows fundamentally alter material dynamics: Pb redistribution transitions from clustered to randomized spatial configurations, while grains develop pronounced in-plane orientation preferences that reciprocally influence Sn crystal alignment. The second reflow produces scallop-type grains with minimized dimensions of 4.0 μm and a thickness of 2.1 μm, with a KAMave of 0.37° and PFmax of 20.5. The third reflow initiates uniform growth of scalloped grains of 7.0 μm with a stable population density, whereas the fifth reflow triggers a semicircular grain transformation of 9.1 μm through conspicuous coalescence mechanisms. This work elucidates multiple reflow IMC growth mechanisms in Pb–free/Pb hybrid solder joints, providing critical theoretical and practical insights for optimizing hybrid technologies and reliability management strategies in high-reliability aerospace electronics.